Asymmetry cointegration and the J-curve: new evidence from Africa. Issue 5 (28th April 2020) - Bahmani-Oskooee, Mohsen; Arize, Augustine Charles
Abstract : Purpose: The purpose is to assess the asymmetric effects of exchange rate changes on the trade balance using data from African nations. Design/methodology/approach: The methodology is based on the most recent development in asymmetry cointegration and error-correction modeling. Findings: While the authors find short-run asymmetric effects in many of the countries in their sample, asymmetry cointegration yields support for the new definition of the J-curve in Algeria, Cameroon, Ethiopia, Morocco, Tanzania and Zambia. Originality/value: This is the first study that applies nonlinear ARDL approach of Shin et al. (2014) using data from each of the 13 countries in Africa.